New Target Genes in Endometrial Tumors Show a Role for the Estrogen‐Receptor Pathway in Microsatellite‐Unstable Cancers. Issue 12 (December 2014) - Ferreira, Ana M.; Tuominen, Iina; Sousa, Sónia; Gerbens, Frans; van Dijk‐Bos, Krista; Osinga, Jan; Kooi, Krista A.; Sanjabi, Bahram; Esendam, Chris; Oliveira, Carla; Terpstra, Peter; Hardonk, Menno; et al.
<x xml:space="preserve">Abstract</x> A genome‐wide search for target genes in endometrial tumors with microsatellite instability. Seven highy mutated genes were found in endometrial cancer; some of them were also found mutated in colorectal and gastric tumors. The most mutated gene, NRIP1, was silenced in an endometrial cell line, which revealed an association with differences in the expression of several genes in the estrogen‐receptor network. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>